A Conceptual Framework for Tiered Intervention in Physical Education - Dauenhauer, Brian; Keating, Xiaofen; Lambdin, Dolly; Knipe III, Robert (Journal of Physical Education, Recreation & Dance, 2017)
Our goal as physical educators is to help all students develop the knowledge, skills and dispositions to be physically active for a lifetime. Despite efforts to address the diverse needs of students through quality physical education, the reality is that some students still need additional support beyond physical education to achieve their full potential. Response to intervention (RTI) is a proactive approach to educational-service delivery that relies on data-driven decision making to identify student needs and to tailor support. Traditionally, RTI has focused on addressing the needs of lower-performing students through tiered interventions. The purpose of this article is to review the basic principles of RTI, discuss how they have been applied in physical education thus far, and expand the conceptual framework so it can be used to address the needs of both higher- and lower-performing students.
_eprint: https://doi.org/10.1080/07303084.2017.1356769
Keywords: dept.hms

Dyspnea - Kreiger, J.; Niekrash, C.; Fitzgerald, C. (The Encyclopedia of Elder Care: The Comprehensive Resource on Geriatric Health and Social Care, 2017)
Praise for the Third Edition:“The third edition of this outstanding resource reflects the many advances in the care of older people that have occurred since the publication of the second edition…The vast bulk of the content is accessible and relevant to an international audience. The indexing and cross-referencing are excellent... Score: 5/5 stars."– Margaret Arthur, Nursing Standard"The information [in this book] is amazing. I reviewed topics in which I have expertise and was very satisfied. This is an excellent addition to my library and I will refer to it often, much like a medical dictionary... Score: 90, 4 Stars."–Doody's Medical Reviews“Provides 273 comprehensive, yet succinct, entries on a variety of topics related to elder care. In addition, many of the entries include see also references that help readers easily navigate the book. Recommended."–Choice: Current Reviews for Academic LibrariesThis expanded, one-of-a-kind reference of more than 250 entries provides a comprehensive guide to all of the essential elements of elder care across a breadth of health and social service disciplines. Responding to the needs of providers, directcare workers, family, and other caregivers, the diverse array of entries included in this encyclopedia recognize and address the complex medical, social, and psychological problems associated with geriatric care. In addition to a brief, accessible summary of each topic, entries include several key references, including web links and mobile apps for additional sources of information.This updated edition contains more than 30 new entries written by renowned experts that address a variety of elder care topics.New to the Fourth Edition:New entries addressing Ethics Consultation, Eye Disorders, Pain – Acute and Chronic, and many othersKey Features:Provides succinct descriptions of over 250 key topics for health and social service cliniciansOffers crucial information for elder care providers across all settings and disciplinesDistills current, evidence-based literature sourcesWritten by nationally recognized expert researchers and cliniciansIncludes links to useful websites and mobile apps
Keywords: dept.hms

Cognitive Performance Does not Limit Physical Activity Participation in the Lifestyle Interventions and Independence for Elders Pilot Study (LIFE-P) - Reid, K. F.; Walkup, M. P.; Katula, J. A.; Sink, K. M.; Anton, S.; Axtell, R.; Kerwin, D. R.; King, A. C.; Kramer, A. F.; Miller, M. E.; Myers, V.; Rosano, C.; et al. (The journal of prevention of Alzheimer's disease, 2017)
We examined whether multiple domains of baseline cognitive performance were associated with prospective physical activity (PA) adherence in the Lifestyle Interventions and Independence for Elders Pilot study (LIFE-P). The LIFE-P study was a ...
Keywords: dept.hms

Association of accelerometry-measured physical activity and cardiovascular events in mobility-limited older adults: The LIFE (Lifestyle Interventions and Independence for Elders) study - Cochrane, S.K.; Chen, S.-H.; Fitzgerald, J.D.; Dodson, J.A.; Fielding, R.A.; King, A.C.; McDermott, M.M.; Manini, T.M.; Marsh, A.P.; Newman, A.B.; Pahor, M.; Tudor-Locke, C.; et al. (Journal of the American Heart Association, 2017)
Background–Data are sparse regarding the value of physical activity (PA) surveillance among older adults-particularly among those with mobility limitations. The objective of this study was to examine longitudinal associations between objectively measured daily PA and the incidence of cardiovascular events among older adults in the LIFE (Lifestyle Interventions and Independence for Elders) study. Methods and Results–Cardiovascular events were adjudicated based on medical records review, and cardiovascular risk factors were controlled for in the analysis. Home-based activity data were collected by hip-worn accelerometers at baseline and at 6, 12, and 24 months postrandomization to either a physical activity or health education intervention. LIFE study participants (n=1590; age 78.9±5.2 [SD] years; 67.2% women) at baseline had an 11% lower incidence of experiencing a subsequent cardiovascular event per 500 steps taken per day based on activity data (hazard ratio, 0.89; 95% confidence interval, 0.84-0.96; P=0.001). At baseline, every 30 minutes spent performing activities ≥500 counts per minute (hazard ratio, 0.75; confidence interval, 0.65-0.89 [P=0.001]) were also associated with a lower incidence of cardiovascular events. Throughout follow-up (6, 12, and 24 months), both the number of steps per day (per 500 steps; hazard ratio, 0.90, confidence interval, 0.85-0.96 [P=0.001]) and duration of activity ≥500 counts per minute (per 30 minutes; hazard ratio, 0.76; confidence interval, 0.63-0.90 [P=0.002]) were significantly associated with lower cardiovascular event rates. Conclusions–Objective measurements of physical activity via accelerometry were associated with cardiovascular events among older adults with limited mobility (summary score > 10 on the Short Physical Performance Battery) both using baseline and longitudinal data. © 2017 The Authors.
30 citations (Crossref) [2023-10-31]
Keywords: Accelerometry; Actigraphy; Age Factors; Aged; Aged; 80 and over; Aging; Article; Cardiovascular; Cardiovascular Diseases; Exercise; Exercise Therapy; Female; Fitness Trackers; Geriatric Assessment; Health Knowledge; Attitudes; Practice; Humans; Incidence; Male; Mobility Limitation; Patient Education as Topic; Physical activity; Predictive Value of Tests; Prognosis; Protective Factors; Risk Factors; Risk Reduction Behavior; Time Factors; United States; accelerometry; actimetry; activity tracker; age; aged; aging; attitude to health; cardiovascular disease; cardiovascular risk; clinical study; clinical trial; confidence interval; controlled study; dept.hms; devices; exercise; female; follow up; geriatric assessment; hazard ratio; health education; human; incidence; kinesiotherapy; lifestyle; major clinical study; male; medical record review; morbidity; multicenter study; patient education; phase 3 clinical trial; physical activity; physical mobility; predictive value; priority journal; prognosis; protection; randomized controlled trial; risk factor; risk reduction; time factor; very elderly; walking difficulty

Sports Injury Prevention: The Role of the Strength and Conditioning Coach - Talpey, S.W.; Siesmaa, E.J. (Strength and Conditioning Journal, 2017)
Prevention of sports injuries is a priority for sport stakeholders across the spectrum of training and competition. Achieving this objective requires a multidisciplinary approach with strength and conditioning coaches playing an important role in the process. When considering sports injury prevention strategies, the role of the strength and conditioning coach can extend beyond observing exercise technique and prescribing training to develop a robust and resilient athlete. This paper provides strength and conditioning coaches with a broad overview of the sports injury prevention process and outlines examples of how strength and conditioning coaches can work to promote and improve athlete safety. © 2017 National Strength and Conditioning Association.
17 citations (Crossref) [2023-10-31]
Keywords: Coaching; Sport safety; Sports medicine; dept.hms

Dose of physical activity, physical functioning and disability risk in mobility-limited older adults: Results from the LIFE study randomized trial. - Fielding, Roger A; Guralnik, Jack M; King, Abby C; Pahor, Marco; McDermott, Mary M; Tudor-Locke, Catrine; Manini, Todd M; Glynn, Nancy W; Marsh, Anthony P; Axtell, Robert S; Hsu, Fang-Chi; Rejeski, W Jack; et al. (PLoS ONE, 2017)
Understanding the minimal dose of physical activity required to achieve improvement in physical functioning and reductions in disability risk is necessary to inform public health recommendations. To examine the effect of physical activity dose on changes in physical functioning and the onset of major mobility disability in The Lifestyle Interventions and Independence for Elders (LIFE) Study. We conducted a multicenter single masked randomized controlled trial that enrolled participants in 2010 and 2011 and followed them for an average of 2.6 years. 1,635 sedentary men and women aged 70-89 years who had functional limitations were randomized to a structured moderate intensity walking, resistance, and flexibility physical activity program or a health education program. Physical activity dose was assessed by 7-day accelerometry and self-report at baseline and 24 months. Outcomes included the 400 m walk gait speed, the Short Physical Performance Battery (SPPB), assessed at baseline, 6, 12, and 24 months, and onset of major mobility disability (objectively defined by loss of ability to walk 400 m in 15 min). When the physical activity arm or the entire sample were stratified by change in physical activity from baseline to 24 months, there was a dose-dependent increase in the change in gait speed and SPPB from baseline at 6, 12, and 24 months. In addition, the magnitude of change in physical activity over 24 months was related to the reduction in the onset of major mobility disability (overall P < 0.001) (highest versus the lowest quartile of physical activity change HR 0.23 ((95% CI:0.10-0.52) P = 0.001) in the physical activity arm. We observed a dose-dependent effect of objectively monitored physical activity on physical functioning and onset of major mobility disability. Relatively small increases (> 48 minutes per week) in regular physical activity participation had significant and clinically meaningful effects on these outcomes., TRIAL REGISTRATION: ClinicalsTrials.gov NCT00116194.
89 citations (Crossref) [2023-10-31] Place: United States Fielding, Roger A. Nutrition, Exercise Physiology, and Sarcopenia Laboratory, Jean Mayer USDA Human Nutrition Research Center on Aging at Tufts University, Boston, MA, United States of America. Guralnik, Jack M. Department of Epidemiology and Public Health, University of Maryland School of Medicine, 4655 W. Baltimore Street, Baltimore, MD, United States of America. King, Abby C. Department of Health Research & Policy, and Stanford Prevention Research Center, Department of Medicine, Stanford University Medical School, Stanford, CA, United States of America. Pahor, Marco. Department of Aging and Geriatric Research, University of Florida College of Medicine, Gainesville, FL, United States of America. McDermott, Mary M. Department of Medicine, Northwestern University Feinberg School of Medicine, 750 N Lake Shore Drive, 10th Floor, Chicago, IL, United States of America. Tudor-Locke, Catrine. Department of Kinesiology, University of Massachusetts Amherst, Amherst, MA, United States of America. Tudor-Locke, Catrine. Pennington Biomedical Research Center, Louisiana State University System, Baton Rouge, LA, United States of America. Manini, Todd M. Department of Aging and Geriatric Research, University of Florida College of Medicine, Gainesville, FL, United States of America. Glynn, Nancy W. Center for Aging and Population Health, Department of Epidemiology, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, PA, United States of America. Marsh, Anthony P. Department of Health and Exercise Science, Wake Forest University, Winston-Salem, NC, United States of America. Axtell, Robert S. Department of Exercise Science, Southern Connecticut State University, New Haven, CT. Hsu, Fang-Chi. Department of Biostatistical Sciences, Division of Public Health Sciences, Wake Forest School of Medicine, Winston-Salem, NC, United States of America. Rejeski, W Jack. Center for Aging and Population Health, Department of Epidemiology, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, PA, United States of America.
Keywords: *Activities of Daily Living; *Disabled Persons; *Exercise; *Mobility Limitation; Activities of Daily Living; Aged; Aged; 80 and over; Article; Disabled Persons; Exercise; Female; Humans; Male; Mobility Limitation; accelerometry; aged; controlled study; daily life activity; dept.hms; disabled person; education program; exercise; exercise intensity; female; human; incidence; major clinical study; male; multicenter study; outcome assessment; peer-reviewed; physical activity; physical activity; capacity and performance; physical disability; physical functioning; physical mobility; physical performance; randomized controlled trial; resistance training; risk assessment; risk factor; sedentary lifestyle; self report; very elderly; walking difficulty; walking speed

Device-measured physical activity as a predictor of disability in mobility-limited older adults - Mankowski, Robert T.; Anton, Stephen D.; Axtell, Robert; Chen, Shyh-Huei; Fielding, Roger A.; Glynn, Nancy W.; Hsu, Fang-Chi; King, Abby C.; Layne, Andrew S.; Leeuwenburgh, Christiaan; Manini, Todd M.; Marsh, Anthony P.; et al. (Journal of the American Geriatrics Society, 2017)
OBJECTIVES: To examine associations between objectively measured physical activity (PA) and incidence of major mobility disability (MMD) and persistent MMD (PMMD) in older adults in the Lifestyle Interventions and Independence for Elders (LIFE) Study. DESIGN: Prospective cohort of individuals aged 65 and older undergoing structured PA intervention or health education. SETTING: The LIFE Study was a multicenter (eight sites) randomized controlled trial designed to compare the efficacy of a long-term structured PA intervention with that of a health education (HE) program in reducing the incidence of MMD in mobility-limited older adults. PARTICIPANTS: LIFE Study participants (n = 1,590) had a mean age +/- standard deviation of 78.9 +/- 5.2, low levels of PA, and measured mobility-relevant functional impairment at baseline. MEASUREMENTS: Activity data were collected using hip-worn 7-day accelerometers at baseline and 6, 12, and 24 months after randomization to test for associations with incident MMD and PMMD (¿= 2 consecutive instances of MMD). RESULTS: At baseline, every 30 minutes spent being sedentary (¡100 accelerometry counts per minute) was associated with higher rate of subsequent MMD (10%) and PMMD (11%) events. Every 500 steps taken was associated with lower rate of MMD (15%) and PMMD (18%). Similar associations were observed when fitting accelerometry-based PA as a time-dependent variable. CONCLUSION: Accelerometry-based PA levels were strongly associated with MMD and PMMD events in older adults with limited mobility. These results support the importance of daily PA and lower amounts of sedentary time levels in this population and suggest that accelerometry may be a useful tool for assessing risk of mobility disability.
25 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000417650000023, lens.org/040-976-851-672-995 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometry; Aged; Aged; 80 and over; Article; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Male; Mini Mental State Examination; Mobility Limitation; Physical Therapy Modalities; Pittsburgh Sleep Quality Index; Sedentary Lifestyle; Time Factors; accelerometry; aged; clinical trial; cohort analysis; controlled study; depression; dept.hms; disability; educational status; ethnic group; exercise; female; functional disease; geriatric assessment; health education; human; major clinical study; major mobility disability; male; marriage; mobility disability; multicenter study; older adults; peer-reviewed; persistent major mobility disability; physical activity; physiotherapy; procedures; prospective study; randomized controlled trial; sedentary lifestyle; sedentary time; sleep quality; time factor; very elderly; walking difficulty

Effects of a Long-Term Physical Activity Program on Activity Patterns in Older Adults. - Wanigatunga, Amal A; Tudor-Locke, Catrine; Axtell, Robert S; Glynn, Nancy W; King, Abby C; McDermott, Mary M; Fielding, Roger A; Lu, Xiaomin; Pahor, Marco; Manini, Todd M (Medicine and science in sports and exercise, 2017)
PURPOSE: To examine the effect of a long-term structured physical activity (PA) intervention on accelerometer-derived metrics of activity pattern changes in mobility-impaired older adults., METHODS: Participants were randomized to either a PA or health education (HE) program. The PA intervention included a walking regimen with strength, flexibility, and balance training. The HE program featured health-related discussions and a brief upper body stretching routine. Participants (n = 1341) wore a hip-worn accelerometer for >=10 h.d for >=3 d at baseline and again at 6, 12, and 24 months postrandomization. Total PA (TPA)-defined as movements registering 100+ counts per minute-was segmented into the following intensities: low-light PA (LLPA; 100-759 counts per minute), high light PA (HLPA; 760-1040 counts per minute), low moderate PA (LMPA; 1041-2019 counts per minute), and high moderate and greater PA (HMPA; 2020+ counts per minute). Patterns of activity were characterized as bouts (defined as the consecutive minutes within an intensity)., RESULTS: Across groups, TPA decreased an average of 74 min.wk annually. The PA intervention attenuated this effect (PA = -68 vs HE: -112 min.wk, P = 0.002). This attenuation shifted TPA composition by increasing time in LLPA (10+ bouts increased 6 min.wk), HLPA (1+, 2+, 5+, and 10+ bouts increased 6, 3, 2, and 1 min.wk, respectively), LMPA (1+, 2+, 5+, and 10+ bouts increased: 19, 17,16, and 8 min.wk, respectively), and HMPA (1+, 2+, 5+, and 10+ bouts increased 23, 21, 17, and 14 min.wk, respectively)., CONCLUSIONS: The PA intervention increased PA by shifting the composition of activity toward higher-intensity activity in longer-duration bouts. However, a long-term structured PA intervention did not completely eliminate overall declines in total daily activity experienced by mobility-impaired older adults.
26 citations (Crossref) [2023-10-31] Place: United States Wanigatunga, Amal A. 1Department of Epidemiology, Johns Hopkins University, Baltimore, MD; 2Department of Kinesiology, University of Massachusetts Amherst, Amherst, MA; 3Exercise Science Department, Southern Connecticut State University, New Haven, CT; 4Department of Epidemiology, University of Pittsburgh, Pittsburgh, PA; 5Department of Health Research and Policy and Department of Medicine, Stanford University, School of Medicine, Stanford, CA; 6Feinberg School of Medicine, Northwestern University, Evanston, IL; 7Nutrition, Exercise Physiology and Sarcopenia Laboratory, Jean Mayer United States Department of Agriculture Human Nutrition Research Center on Aging, Tufts University, Boston, MA; 8Department of Biostatistics, University of Florida, Gainesville, FL; and 9Department of Aging and Geriatric Research, University of Florida, Gainesville, FL.
Keywords: *Aged/ph [Physiology]; *Exercise; *Health Promotion; ACCELEROMETER; ACTIVITY BOUTS; Accelerometry; Age Factors; Aged; Aged; 80 and over; ELDERLY; Exercise; Female; Health Promotion; Humans; LIGHT-INTENSITY PHYSICAL ACTIVITY; Male; Mobility Limitation; PHYSICAL ACTIVITY INTERVENTION; Program Evaluation; Sedentary Behavior; Sedentary Lifestyle; accelerometry; age; aged; clinical trial; controlled study; dept.hms; exercise; female; health promotion; human; male; multicenter study; peer-reviewed; physiology; program evaluation; randomized controlled trial; sedentary lifestyle; very elderly; walking difficulty

Household support for physical activity in adolescent girls recruited from lower SES neighborhoods - Rupp, Kristie; Taverno Ross, Sharon E.; Gary-Webb, Tiffany L.; Akiva, Thomas; Jakicic, John M. (Medicine & Science in Sports & Exercise, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms

Perceptions of PEP grant influences on CSPAP implementation - Berei, Catherine P.; Karp, Grace Goc; Olsen, Simon; Fennell, Marcis; Drake, Elisa (Research Quarterly for Exercise and Sport, 2017)
tex.eissn: 2168-3824 tex.unique-id: ISI:000401115400154
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Guideposts and roadblocks to the career-long scholarly engagement of physical education teacher education faculty - Berei, Catherine P; Pratt, Erica; Parker, Melissa; Shephard, Kevin; Liang, Tanjian; Nampai, Udon; Neamphoka, Guntima (Research Quarterly for Exercise and Sport, 2017)
Purpose: Scholarship is essential for the growth and development of the physical education field. Over time, scholarship expectations have changed, forcing faculty members to alter time spent for research, teaching, and service. Social-cognitive career theory (SCCT) presents a model for understanding performance and persistence in an occupational environment. The interconnected aspects of SCCT have different emphasis related to self-efficacy, outcome expectations, or personal goals pursuit. This study explored physical education teacher education (PETE) faculty members' continuing engagement in scholarly activity through SCCT. Method: Data collection included interviews with 9 senior PETE faculty members who met the criteria for “productive scholars over time.” Curriculum vitae were collected to verify productivity. Results: Data analysis revealed guidepost themes that included collaborating, finding balance, defining a research process, and maintaining a strong work ethic. Roadblocks encountered included other obligations and lack of support for research. Conclusions: Participants demonstrated strong self-efficacy; held high, positive expectations for success; and set very specific, clear, and deliberate goals. Participant behavior was moderated by their personal attributes (capacity to build relationships, set goals, and maintain interest and passion) and was tempered by the environments in which they worked. Fostering similar behaviors has the potential to guide future and current PETE faculty members in creating supportive and encouraging atmospheres for sustained productivity. The lack of literature relating to this topic warrants the need for more research exploring the influential factors and benefits gained from sustained scholarly productivity over time for PETE faculty members.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-589-102-475-389 tex.type: [object Object]
Keywords: Academic publishing; Ethics; Professional; Female; Goals; Humans; Male; Physical Education and Training; Research; School Teachers; Self Efficacy; adult; atmosphere; barriers to productivity; career; curriculum; data analysis; dept.hms; expectation; faculty research productivity; female; higher education research; human; human experiment; interview; male; medical ethics; motivation; peer-reviewed; physical education; productivity; psychology; publishing; research; school teacher; self concept; teacher training; theoretical study

Integrating CSPAP into the PETE programs at Southern Connecticut State University and Central Connecticut State University - Ciotto, Carol M; Fede, Marybeth H (The Journal of Physical Education, Recreation & Dance, 2017)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-884-940-096-419 tex.type: [object Object]
Keywords: dept.hms

Cultivating leadership, pedagogy and programming for CSPAP and healthy, active lifestyles at the University of Idaho. - Karp, Grace Goc; Brown, Helen; Scruggs, Philip W; Berei, Catherine P (The Journal of Physical Education, Recreation & Dance, 2017)
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/038-401-000-460-370 tex.type: [object Object]
Keywords: dept.hms

Cardiovagal tone: A predictor of heart rate adjusted augmentation index in men but not in women - Latchman, Peter L.; Thiel, Robert; Gates, Gregory; Zhu, Weili; Axtell, Robert; Gardner, Kenneth; Lunn, William; DeMeersman, Ronald (Open Journal of Molecular and Integrative Physiology, 2017)
2 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

Concurrent validation of the tandem walk test as a measure of dynamic walking balance in a healthy population - Robertson, Marc; Gregory, Robert (Physical Therapy and Rehabilitation, 2017)
4 citations (Crossref) [2023-10-31] Citation Key Alias: robertsonConcurrentValidationTandem2017a
Keywords: dept.hms; peer-reviewed